Penggunaan Flipbook Sebagai Media Akuisisi Keterampilan Berpikir Kritis Mahasiswa Iain Curup - Fajri Mediansyah; Warsah, Idi; Daheri, Mirzon (Universitas Majalengka, 2024)
This study aims to analyze the use of flipbook media in developing critical thinking skills of IAIN Curup students. The research uses a qualitative approach with a case study design. Data was obtained through observation, interviews, and documentation from two lecturers and five students of the PAI Study Program. Data analysis is carried out through the process of condensation, presentation, and verification, with validation through triangulation of sources and techniques. The results of the study show that flipbook planning is carried out by integrating critical thinking indicators, such as analysis, evaluation, and creativity, so as to produce effective and interesting learning media. In the implementation stage, lecturers support students' critical thinking skills through: (1) initial activities that focus on clarification, analysis, inference, evaluation, and communication; (2) core activities that include analysis and identification in case studies and assignments; and (3) closing activities that emphasize evaluation and self-regulation. The evaluation stage shows that the use of flipbooks increases the effectiveness and learning activities, as evidenced by learning outcomes, assessment rubrics, and interactions during the learning process. In conclusion, flipbook media is proven to be a useful tool for acquiring students' critical thinking skills, supporting learning that is more active, effective.